The Application of Aiken's V Method for Evaluating the Content Validity of Instruments that Measure the Implementation of Formative Assessments - Nurjanah, Siti; Istiyono, Edi; Widihastuti, Widihastuti; Iqbal, Muhammad; Kamal, Saefudin (Universitas Negeri Semarang, 2023)
This study aims to analyze the content validity of the measuring instrument used for formative assessment implementation by utilizing the Aiken method. The selection of formative assessment was based on the consensus within experts that it offers significant enhancements to the progression of classroom learning. Nevertheless, there is currently no valid instrument available to measure it. The instrument under study encompasses three key dimensions: perceptions, practices, and challenges. The instrument consists of a closed-ended questionnaire with 37 items and an open-ended questionnaire with 2 items. The content validity was evaluated by three raters who are highly experienced in their respective disciplines. After doing a quantitative study of the Aiken's V value, it was determined that all items of the instrument for implementing formative assessment were deemed valid. According to the qualitative analysis, raters provided some modest revisions for certain items. Overall, the instrument used to assess the implementation of formative assessment is deemed valid through content validity analysis relying on Aiken's method. Instructors, researchers, and policy makers can utilize the findings of this study to obtain information regarding the implementation of formative assessment through the utilization of the measuring instrument employed in this study.